THE POWER OF DIGITAL INFLUENCERS - HOW BRAND ENGAGEMENT AND EXPECTED VALUE DRIVE PURCHASE INTENTION ON SOCIAL MEDIA: CASE OF INDONESIA - Muhammad Iffan; Umi Narimawati; Agus Riyanto (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
The research aims to find out the influence of digital influencers on purchase intention through brand engagement and brand expected value on Instagram users. Validity and reliability tests as well as path analysis are used in this study. Instagram users who followed social media influencers were participants in the study. The data analysis methods used in this study are loading factor, AVE, cross-loading, and composite reliability tests. Data analysis results show that all variables have good validity and reliability, and the results of hypothetical testing show that digital influencers, brand engagement, and brand expected value have significant influence on purchase intention on Instagram users. This suggests that the digital influence can have positive chain effects, such as increasing consumer engagement with brands, creating expected value for brands, and encouraging customers' desire to buy products. It provides a deeper understanding of how influencer-based marketing strategies can impact consumer behavior related to e-commerce.